Tissue factor-positive microparticles: Cellular origin and association with coagulation activation in patients with colorectal cancer - Hron, Gregor; Kollars, Marietta; Weber, Heinz; Sagaster, Verena; Quehenberger, Peter; Eichinger, Sabine; Kyrle, Paul A.; Weltermann, Ansgar (Thrombosis and Haemostasis, 2007)
The pathogenesis of hypercoagulability in cancer is not entirely understood. We hypothesized that in cancer patients circulating tissue factor-positive microparticles (TF+ MPs) are increased and associated with hemostatic system activation. In 20 patients with advanced colorectal cancer and in 20 age- and sex-matched controls, number and cellular origin of TF+ MPs were determined in plasma by flow cytometry. D-dimer was determined as an indicator of hemostatic system activation. Compared to controls, the median (interquartile range) number of TF+ MPs was two-fold higher in cancer patients: 25.9 (15.4 – 42.0) × 103 /ml plasma versus 13.1 (11.9 – 19.7) × 103 /ml plasma, p = 0.007. This was mainly due to a higher amount of TF+ MPs from platelets (13.4 [5.0 – 17.4] × 103 /ml plasma vs. 5.8 [4.5 – 7.5] × 103 /ml plasma, p = 0.017). TF+ MPs correlated with D-dimer (ρ = 0.48, p = 0.002). High levels of TF+ MPs in cancer patients and their correlation with D-dimer suggest that TF+ MPs might be involved in hemostasis activation in cancer patients.
Keywords: Cancer; microparticles; tissue factor; hemostasis; platelets